Chitooligosaccharides from shrimp shell chitosan prepared using H2O2 or ascorbic acid/H2O2 redox pair hydrolysis: characteristics, antioxidant and antimicrobial activities. (21st March 2022) - Mittal, Ajay; Singh, Avtar; Hong, Hui; Benjakul, Soottawat
Summary: Chitooligosaccharides (COS) prepared from shrimp ( Litopenaeus vannamei ) shell chitosan using H2 O2 at different concentrations or ascorbic acid (AsA)/H2 O2 redox pair at various concentration ratios using different hydrolysis times and temperatures were characterised. COS produced by 0.05/0.1 (M/M) of AsA/H2 O2 redox pair (COS‐RP) showed higher DPPH and ABTS radical scavenging activities, FRAP, metal chelating activity and ORAC ( P  < 0.05). Based on fourier transform infrared (FTIR) spectra, COS‐HP and COS‐RP had slight difference between functional groups. COS‐RP had low degree of polymerisation (2–8) and average molecular weight (0.7 kDa). Intermolecular hydrogen bonds were broken, and crystallinity of chitosan was decreased after hydrolysis. COS‐RP showed higher zone of inhibition toward tested bacteria than COS‐HP ( P  < 0.05). 1 H‐NMR and 13 C‐NMR spectra also reconfirmed that no drastic alteration in chemical structure of both COS samples took place. Overall, COS prepared using AsA/H2 O2 redox pair reaction was recommended due to its higher antioxidant and antimicrobial activities than that using H2 O2 alone. Abstract : An overview of preparation, characterisation, and bioactivities of chitooligosaccharides.